Polycyclic aromatic hydrocarbons (PAH) and their genotoxicity in exhaust emissions from a diesel engine during extended low-load operation on diesel and biodiesel fuels. (May 2015) - Vojtisek-Lom, Michal; Pechout, Martin; Dittrich, Luboš; Beránek, Vít; Kotek, Martin; Schwarz, Jaroslav; Vodička, Petr; Milcová, Alena; Rossnerová, Andrea; Ambrož, Antonín; Topinka, Jan
Abstract: This paper investigates the effects of emissions including carcinogenic polycyclic aromatic hydrocarbons (cPAH) of a conventional diesel engine without a particle filter. Experiments were carried on during extended idle and during a loaded operation immediately following the extended idle. Extended low-load operation of diesel engines due to idling and creep at border crossings, loading areas and in severe congestion has been known to deteriorate the combustion and catalytic device performance and to increase the emissions of particulate matter (PM). A conventional diesel engine was coupled to a dynamometer and operated on diesel fuel and neat biodiesel alternately at idle speed and 2% of rated power and at 30% and 100% load at intermediate speed. Exhaust was sampled on fiber filters, from which the content of elemental and organic carbon and polycyclic aromatic hydrocarbons (PAH), including cPAH and benzo[a]pyrene (B[a]P) have been determined. The emissions of cPAH and B[a]P have increased 4–6 times on diesel fuel and by 4–21% on biodiesel during extended idling relative to a short idle and 8–12 times on diesel fuel and 2–20 times on biodiesel during subsequent operation at full load relative to stabilized operation at full load. The total "excess" cPAH emissions after the transition to full load were on the same order of magnitude as the total "excess" cPAH during extended idling. The absolute levels of PAH, cPAH and B[a]P emissions under all operating conditions were lower on biodiesel compared to diesel fuel. Genotoxicity of organic extracts of particles was analysed by acellular assay with calf thymus DNA (CT-DNA) and was consistently higher for diesel than for biodiesel. The exhaust generated during extended idle and subsequent full load exhibited the highest genotoxicity for both fuels. These two regimes are characterized by significant formation of cPAH as well as other DNA reactive compounds substantially contributing to the total genotoxicity. Oxidative DNA damage by all tested extracts was negligible. Graphical abstract: Highlights: Carcinogenic PAH (cPAH) an order of magnitude higher during extended vs. short idle. Extended idle increases cPAH during subsequent loaded operation. Increase in cPAH much smaller on neat biodiesel. Neat biodiesel had lower cPAH than diesel under all conditions. Neat biodiesel exhibited lower genotoxicity than diesel under all operating modes.